Biocompatible agar/xanthan gum composite films: Thermal, mechanical, UV, and water barrier properties. (9th July 2019) - Rukmanikrishnan, Balasubramanian; Rajasekharan, Satish Kumar; Lee, Jintae; Lee, Jaewoong
Abstract : Binary composite films were prepared from agar (A) and xanthan gum (X) with different weight percentages. The composite films were transparent, lightweight, eco‐friendly, and biodegradable. The structure and morphology of the prepared agar and AX composite films were confirmed by Fourier transform infrared spectroscopy (FT‐IR), X‐ray powder diffraction (XRD), and scanning electron microscopy (SEM) technique. The glass transition temperature (Tg ) and melting temperature (Tm ) of the AX composite films was slightly improved, when compared with the neat agar. Thermogravimetric analysis (TGA) analysis showed a considerable increment in the char yield and an improved thermal stability. The tensile strength was in the range of 25 to 40 MPa, and elongation at break was in the range of 28.9 to 39.4%. Though, the water vapor permeability (WVP) value reduced in the composite films the difference was not significant. From the mechanical studies, we can deduce that agar and xanthan gum are compatible and miscible with one another leading to prospects of their composite films being considered for different biomedical and packaging applications.